2003
DOI: 10.1111/j.1365-2621.2003.tb05705.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Modeling of Dielectric Properties of Turkey Meat

Abstract: The dielectric properties of turkey meat at water activities of 0.84 to 0.98 were measured at 2450 and 915MHz. Equations were developed as a function of temperature, moisture, water activity, and ash, and compared to literature equations. Unexpected results were: as the water activity decreased or ash increased, the dielectric constant increased with temperature, and dielectric loss factor of reduced moisture samples was determined by moisture not ash. It is theorized that the effect of temperature on dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
3
4
0
1
Order By: Relevance
“…Trends for 100% back fat seemed also to be driven by the phase transitions, and the low absolute values for the dielectric constant arose from the low content in moisture and ash. The general trends for the evolution of the dielectric constant in patties containing lean meat and lean meat and fat mixtures agree with those found by Bircan and Barringer (2002) for entire muscles, Tong and Lenzt (1993) for bentonite pastes, Sipahiouglu and others (2003b) for brined turkey meat, Gunasekaran and others (2005) for ground beef, and Brunton and others (2005) for raw beef biceps femoris . This trend most likely means a growing penetration depth during heating (Van Remmen and others 1996).…”
Section: Resultssupporting
confidence: 83%
“…Trends for 100% back fat seemed also to be driven by the phase transitions, and the low absolute values for the dielectric constant arose from the low content in moisture and ash. The general trends for the evolution of the dielectric constant in patties containing lean meat and lean meat and fat mixtures agree with those found by Bircan and Barringer (2002) for entire muscles, Tong and Lenzt (1993) for bentonite pastes, Sipahiouglu and others (2003b) for brined turkey meat, Gunasekaran and others (2005) for ground beef, and Brunton and others (2005) for raw beef biceps femoris . This trend most likely means a growing penetration depth during heating (Van Remmen and others 1996).…”
Section: Resultssupporting
confidence: 83%
“…In the past decades, the dielectric properties of various materials, such as fruits and vegetables, meats, starches, and other foods (Nelson et al, 1994;Sipahioglu, et al, 2003;Wang et al, 2003;Liu et al, 2009), have been investigated. The major factors that influence the dielectric properties of materials, such as frequency, temperature, moisture content and salt content, have been studied and reported (Berbert et al, 2001;Feng et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that it is important to maintain good interfacial contact between the sample and the probe during phase change. In earlier studies [8][9][12][13], a cylindrical jacketed cell was used to maintain the temperature of the sample by circulating a fluid from a temperature-controlled fluid bath. As the other end of the probe was exposed to room temperature, the sample temperature at the contact point with the probe may not be exactly the same as the fluid temperature.…”
Section: Evaluation Calibration At 25 °Cmentioning
confidence: 99%
“…For food products, which are generally liquid or semi-solid materials, open-ended coaxial line probes have been used for broadband permittivity measurement. Many food materials including shrimp [5], macaroni and cheese [6], whey protein gel [7][8], ground whole-wheat flour [7], apple juice [7], turkey meat [9], vegetables [10], chicken breast [11], eggs [12], and gellan gel [13] have been measured using the coaxial line method as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%